Mendeley Reference Management Training on Students’ Thesis and Scientific Articles - Fadlilah Fadlilah; Mahmud MY; Hamdan Hamdan; Ahmad Ansori; Fransisko Chaniago; Fiqhi Fiqhi; Husarida Husarida; Yuliana Afifah; Suci Fitriani (Jurnal Pengabdian UNDIKMA, 2023)
This service aims to practice using Mendeley reference management in Thesis and Scientific Articles of Islamic Education Management students of UIN Sulthan Thaha Saifuddin Jambi to comply with the ethical principles of student scientific publications. This service involved all students in semester VI who would be dealing with making final assignments to hold a bachelor's degree with the observation method, namely pre-test activities, the counseling method through PowerPoint material, the practical approach that was direct training, and evaluation activities through post-test. The results of the service that had been carried out in the use of Mendeley reference management for students could be stated that 100% of students could operate Mendeley applications both based on Mendeley Web and Mendeley Desktop in carrying out citations and making automatic bibliography on each student's Thesis and Scientific Articles.